2006
DOI: 10.1111/j.1469-0691.2006.01441.x
|View full text |Cite
|
Sign up to set email alerts
|

A large multi-pathogen waterborne community outbreak linked to faecal contamination of a groundwater system, France, 2000

Abstract: A large waterborne outbreak of infection that occurred during August 2000 in a local community in France was investigated initially via a rapid survey of visits to local physicians. A retrospective cohort study was then conducted on a random cluster sample of residents. Of 709 residents interviewed, 202 (28.5%) were definite cases (at least three liquid stools/day or vomiting) and 62 (8.7%) were probable cases (less than three liquid stools/day or abdominal pain). Those who had drunk tap water had a three-fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(89 citation statements)
references
References 36 publications
(50 reference statements)
3
84
0
2
Order By: Relevance
“…In South Bass Island on Lake Erie in Ohio, groundwater contamination originated from wastewater-treatment facilities and septic tank overflows due to precipitation events (Fong, 2007). In southwestern France, a massive community outbreak of campylobacteriosis was part of a multi-pathogen drinking water contamination event due to agricultural run-off and malfunctions in the water treatment facilities for the village of Gourdon (Gallay, 2006). In both cases, water contamination derived from human and animal sources of Campylobacter.…”
Section: Groundwatermentioning
confidence: 99%
“…In South Bass Island on Lake Erie in Ohio, groundwater contamination originated from wastewater-treatment facilities and septic tank overflows due to precipitation events (Fong, 2007). In southwestern France, a massive community outbreak of campylobacteriosis was part of a multi-pathogen drinking water contamination event due to agricultural run-off and malfunctions in the water treatment facilities for the village of Gourdon (Gallay, 2006). In both cases, water contamination derived from human and animal sources of Campylobacter.…”
Section: Groundwatermentioning
confidence: 99%
“…Outbreaks of viral acute gastroenteritis by consumption of contaminated water have been frequently reported in the world, and viruses are known as the etiological agents for the infectious gastroenteritis (Divizia et al 2004). While rotaviruses, astrovirus, and norovirus have been involved in these outbreaks (Hung et al 1984;Boccia et al 2002;Divizia et al 2004;Hoebe et al 2004;Gallay et al 2006;Hewitt et al 2007;Martinelli et al 2007;Maunula et al 2009), routine procedures for monitoring these viruses in water samples had not been drawn up for the water-microbiology screening panel. Sewage water contains much higher numbers of viruses (Meleg et al 2006) and sewage workers frequently exposed to raw sewage were found to be at higher risk of intestinal disease (Rylander 1999;Venczel et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…5,19 Therefore, other bacterial, viral and parasitic agents must be examined together with the norovirus. In this study, examples of patients evaluated for bacterial, viral and parasitic agents, but a positive result was not obtain.…”
Section: Discussionmentioning
confidence: 99%